Negotiating Masculinity in Early Childhood Education: Relational Authority and Workforce Diversification among Male Teachers in Indonesia - Selvi, Issaura Dwi; Suyadi; Ro'fah; Purnama, Sigit (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2025)
Purpose – This study examines how male teachers in Early Childhood Education (ECE) renegotiate masculine identity within a historically feminized profession in Indonesia. It demonstrates how authority is reorganized through relational pedagogy and emotional regulation, situating masculinity negotiation within debates on workforce diversification, teacher quality, and inclusive education under SDG 4.Design/methods/approach – This study employed an Interpretative Phenomenological Analysis (IPA) design to explore the lived experiences of six male Early Childhood Education teachers from three regions. Primary data were generated through in depth semi structured interviews, which formed the basis for idiographic thematic analysis and cross case interpretation. A national Focus Group Discussion involving 162 male teachers was observed as contextual support without contributing to theme development. Analysis was conducted through case by case interpretation informed by hegemonic masculinity theory, supported by audit trails and reflexive documentation to ensure trustworthiness.Findings – The findings reveal a layered reconfiguration of masculinity across micro, meso, and macro contexts. At the classroom level, authority is stabilized through emotional self-regulation and co-regulative interaction rather than dominance. At the symbolic level, leadership and paternal imagery are recalibrated through dialogical engagement and professional competence, including STEM-based pedagogical practice. At the collective level, professional networks function as stabilizing infrastructures that reframe individual doubt as structural negotiation. Within Muslim-majority society, moral vocabulary operates as a contextual resource that reinforces professional legitimacy without displacing the central focus on educational quality.Research implications/limitations – The study contributes to international scholarship by demonstrating how masculinity in ECE can be institutionally stabilized through relational practice and communal embedding in Global South contexts. Limitations include the qualitative and context-bound design, absence of cross-national comparison, and reliance on teachers who remain in the profession, suggesting directions for longitudinal and comparative research.Practical implications – The findings inform teacher education and policy discussions on workforce diversification, highlighting how gender-sensitive pedagogy, emotional literacy, and professional community support can enhance retention and legitimacy of male teachers in ECE systems.Originality/value – By identifying the micro-level mechanisms through which masculine authority is reconstructed in everyday ECE practice, this study advances understanding of gender negotiation within Muslim-majority societies.Paper type Phenomenological Qualitative Study